Intra-articular acetabular osteochondroma in patients with multiple hereditary exostoses. Issue 1 (15th June 2021) - Choudhry, Ashima; Gimm, Geunwu; Kang, Ho Won; Shin, Chang Ho; Yoo, Won Joon; Choi, In-Ho; Cho, Tae-Joon
Abstract : We report three additional cases of intra-articular acetabular osteochondroma in multiple hereditary exostoses patients in order to raise the awareness of this rare location, to prompt early diagnosis, and to present various treatment options according to the patient's condition. A 2.5-year-old boy presenting with an out-toeing gait had a large acetabular osteochondroma causing lateral displacement of the femoral head and acetabular dysplasia. Mass excision through hip subluxation via anterior approach and concomitant Dega osteotomy resulted in a congruent, well-developed, and well-covered hip joint at 11-year follow-up. A 10-year-old boy showing a pedunculated osteochondroma arising from the triradiate cartilage was successfully treated by arthroscopic excision. Normal development of the hip joint was observed at skeletal maturity. A 6-year-old boy presented with a painless limp. Acetabular osteochondroma could be confirmed by computed tomography scan, which was excised through hip subluxation by anterior approach. Persistent coxa valga and femoral head uncovering were addressed by femoral varization osteotomy at 9 years of age. A high index of suspicion is required to detect a lesion at this rare location. Various procedures may be considered according to the pathoanatomy. Acetabular dysplasia, coxa valga, and femoroacetabular impingement by femur neck mass, if associated, should be addressed in due time.